Competências transmídia : entre usos e percepções dos estudantes do Colégio Estadual Barão de Mauá em Aracaju/SE - Santos, Mirabel dos (2020)
With the emergence of the network and digital media, messages started to circulate on different platforms, demanding from their users / readers new skills to use the various hardware, software and their protocols. Information and communication technologies have been transforming the subjects' cognition, demanding - in view of the consumption of distributed content - in addition to different and specific skills, these called transmedia skills. The present dissertation, based on the scenario found at the Colégio Estadual Barão de Mauá (Aracaju-SE), aimed to map the transmedia skills present in the schooling process ofstudents in the 3rd Grade of High School of the referred school, contributing to guide practices in the formal space education, more consonant with the current media ecology and, consequently, with the profile of the students in question. Accounting for the relationships between digital media, technology and education in a hyperconnected era, we sought to understand how these adolescents are consuming, producing, sharing, creating and learning in digital environments. Therefore, based on the theoretical-methodological framework of the Transmedia Literacy Project, developed by Carlos A. Scolari and team, the present work, from a deductive perspective and a qualitative approach with an ethnographic bias, made use of techniques such as participant and online observation, online questionnaire and semi-open in-depth interview. The results confirmed that transmedia skills are present in the students schooling process, that the smartphone emerges as the main technological artifact used in digital social media as the foremost channel for disseminating their content.